The role of probiotics in the treatment of depressive disorders. A critical review - Głaz, Aneta; Knop-Chodyła, Kinga; Kochanowska-Mazurek, Anna; Wach, Damian; Piasecka, Zuzanna; Wesołek, Ewelina; Kasztelan-Szczerbińska, Beata; Skrzydło-Radomańska, Barbara (Journal of Education, Health and Sport, 2023)
Depressive disorders are a widespread problem in modern medicine. According to current data from the World Health Organisation, an estimated 280 million people worldwide suffer from depression. In recent years, there have been reports of a correlation between the composition of the gut microbiota and the development of depressive disorders and attempts to modify it through the use of psychobiotics. The literature from the PubMed database published between 2018-2023 has been explored. 596 articles were selected based on the keywords "probiotics" and "depression". Six randomized clinical trials were finally included in the analysis. As defined elsewhere, psychobiotics are probiotic bacteria which supplemented in adequate amounts, interact with the gut-brain axis and show beneficial effects on patients’ mental health. Results from recent RCTs suggest that daily probiotic supplementation significantly reduces the severity of depression compared to placebo (p<0.05). Additionally, this effect may be enhanced by the combined use of a probiotic with a prebiotic. Furthermore, some researchers indicate that probiotics may lead to significant improvements in cognitive function in patients suffering from depressive disorders. In conclusion, intestinal dysbiosis may be an important factor leading to the development of mental illness. Results of recent studies suggest that specific strains of probiotic bacteria may offer therapeutic benefits in the treatment of the aforementioned disorders. However, further clinical studies are needed to objectively confirm the relationship between gut microbiota composition and the development of depression.